Rechengraphen: Eine Darstellungsform für Rechenwege von Schülergruppen (mathematica didactica, 2007)
In order to describe how students calculate a given mathematical task in an aggregated way statistical indicators are widely used. The real calculations get lost. In this paper calculation graphs are introduced. They show all essential calculations of a group of persons and remain easily understandable. Calculation graphs still contain enough information for diagnosis and further interpretations.